Strategi Pengembangan Sumber Daya Manusia untuk Meningkatkan Kualitas Kerja - Najwaturrohmah Najwaturrohmah; Gina Mardiah Putri R.; Zahra Nur Afni; Sri Mulyeni (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
In the dynamic era of information technology disruption and globalization, organizations face increasingly fierce competition. High-quality human resources (HR) represent the core strength for organizations to survive and compete, demanding well-designed development strategies. This study aims to comprehensively analyze various effective HR development strategies to enhance work quality, productivity, and operational efficiency across various organizational sectors. The method employed in this research is a literature study (library research). Data collection was conducted by deeply reviewing ,and analyzing, sourced from various online publications. The results indicate that HR development strategies in the corporate sector are effectively realized through a combination of regular technical training, employee rotation policies, and KPI-based coaching and mentoring programs to implement the principle of